MODEL APLIKASI AKSARA LONTARA BERBASIS HTML SEBAGAI SALAH SATU SOLUSI PEMERTAHANAN BAHASA DAERAH - Baso, Yusring Sanusi (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
The aim of this article is to show a prototype of Lontara’s alphabet characters (character fonts used by the Bugis-Makassar in South Sulawesi). This application of Lontara alphabet can be used either on windows operating system or internet hypertext. The method used in this research is Research and Development (R & D). The researcher used three stages. First; conducted a need analysis to look at the gap between what is expected with and what happened over the use of Lontara’s applications based on windows operating system. The gap of this study is to look for the difference between what should happen with the real reality. Second; developed and designed of applications based hypertext for lontara alphabet in accordance with the results of the needs analysis in the first stage. Third, the author will validate and test this aplication through test one-on-one, test in a small and large group. The product fo this research is an application can be used in communicating via e-mail, social media, and other hypertext platform. The other product is a book that explains Lontara’s application and its integration with other applications to create interactive files, for example with hot potatoes program. Tujuan penelitian ini adalah untuk menunjukkan prototype aplikasi aksara Lontara (karakter huruf Bahasa daerah Bugis-Makassar di Sulawesi Selatan). Aplikasi aksara ini dapat dijalankan pada system operasi window dan platform hyperstext. Metode Research and Development (R&D) dipilih digunakan dalam penelitian ini. Dalam penelitian R & D ini, tiga tahapan dilakukan peneliti, yaitu 1) melakukan analisis kebutuhan untuk mengenalipemertahanan bahasa Bugis-Makassar yang terjadi di lapangan dan bagaimana melakukan usaha pemertahanan Bahasa daerah, 2) merancang dan membuat aplikasi aksara Lontara berbasis hypertext, dan 3) melakukan validasi atas aplikasi hypertext tersebut dengan uji satu-satu, uji kelompok kecil dan uji kelompok besar. Produk dari penelitian ini berupa aplikasi aksara Lontara berbasis hypertext yang dapat digunakan berkomunikasi baik melalui email atau media social facebook. Aplikasi ini juga dapat diintegrasikan dengan berbagai aplikasi interaktif lainnya berbasis atau berplatform berbasis html lainnya, misalnya program Hot Potatoes.